Migration and Health Systems performance in low- and middle- income countries - Khama, Stephen (Department of Public Health and Family Medicine, 2023)
Increased migration is one of the main challenges impacting on health system performance. The World Health Organisation (WHO) framed responsiveness, fair financing, and equity as the intrinsic goals of a health system. In line with this framework, we attempted to map existing research on migration and health system performance. A qualitative systematic review was conducted. We followed the processes indicated for evidence mapping synthesis reviews, which included choosing the scope and research topic, searching, and selecting evidence, reporting findings, and identifying the evidence. We improved the primary review by first performing a brief scoping review, which served as the analytical basis for the systematic review extraction process. Articles found during the scoping review were evaluated again during the bigger systematic review phase. We refined the study's eligibility criteria as well as the data extraction items. Seventy-two articles were considered for the review. Out of this total (55/72) were published between 2016 and 2021. Our analysis showed fairness in financing, weak governance and leadership, the absence of a universally acceptable definition of migration, limited access of migrants to healthcare, equity, health worker attitude towards migrants, dignity, and health care quality to migrants as key challenges that affect health system performance. The mapping exercise shows more literature on migration and health system performance, but also shows gaps requiring urgent attention, including integration of the health system goals in implementing health interventions. We conclude that countries are recognising the challenges of migration on health system performance. Migration is slowly being included in national health policies in low- and middle- income countries, however challenges to implementation of such policies exist. Migration is recognised as a human right and the ethical obligation of health institutions. More agenda setting and funding for bridging work on migration and health system performance is recommended.